# 2003 AIME II Problems/Problem 15

## Problem

Let $$P(x) = 24x^{24} + \sum_{j = 1}^{23}(24 - j)(x^{24 - j} + x^{24 + j}).$$ Let $z_{1},z_{2},\ldots,z_{r}$ be the distinct zeros of $P(x),$ and let $z_{k}^{2} = a_{k} + b_{k}i$ for $k = 1,2,\ldots,r,$ where $a_{k}$ and $b_{k}$ are real numbers. Let

$\sum_{k = 1}^{r}|b_{k}| = m + n\sqrt {p},$

where $m, n,$ and $p$ are integers and $p$ is not divisible by the square of any prime. Find $m + n + p.$

## Solution

This can be factored as:

$$P(x) = x\left( x^{23} + x^{22} + \cdots + x^2 + x + 1 \right)^2$$

Note that $\left( x^{23} + x^{22} + \cdots + x^2 + x + 1 \right) \cdot (x-1) = x^{24} - 1$. So the roots of $x^{23} + x^{22} + \cdots + x^2 + x + 1$ are exactly all $24$-th complex roots of $1$, except for the root $x=1$.

Let $\omega=\cos \frac{360^\circ}{24} + i\sin \frac{360^\circ}{24}$. Then the distinct zeros of $P$ are $0,\omega,\omega^2,\dots,\omega^{23}$.

We can clearly ignore the root $x=0$ as it does not contribute to the value that we need to compute.

The squares of the other roots are $\omega^2,~\omega^4,~\dots,~\omega^{24}=1,~\omega^{26}=\omega^2,~\dots,~\omega^{46}=\omega^{22}$.

Hence we need to compute the following sum:

$$R = \sum_{k = 1}^{23} \left|\, \sin \left( k\cdot \frac{360^\circ}{12} \right) \right|$$

Using basic properties of the sine function, we can simplify this to

$$R = 4 \cdot \sum_{k = 1}^{5} \sin \left( k\cdot \frac{360^\circ}{12} \right)$$

The five-element sum is just $\sin 30^\circ + \sin 60^\circ + \sin 90^\circ + \sin 120^\circ + \sin 150^\circ$. We know that $\sin 30^\circ = \sin 150^\circ = \frac 12$, $\sin 60^\circ = \sin 120^\circ = \frac{\sqrt 3}2$, and $\sin 90^\circ = 1$. Hence our sum evaluates to:

$$R = 4 \cdot \left( 2\cdot \frac 12 + 2\cdot \frac{\sqrt 3}2 + 1 \right) = 8 + 4\sqrt 3$$

Therefore the answer is $8+4+3 = \boxed{015}$.

## Solution 2

Note that $x^k + x^{k-1} + \dots + x + 1 = \frac{x^{k+1} - 1}{x - 1}$. Our sum can be reformed as $$\frac{x(x^{47} - 1) + x^2(x^{45} - 1) + \dots + x^{24}(x - 1)}{x-1}$$

So $$\frac{x^{48} + x^{47} + x^{46} + \dots + x^{25} - x^{24} - x^{23} - \dots - x}{x-1} = 0$$

$x(x^{47} + x^{46} + \dots - x - 1) = 0$

$x^{47} + x^{46} + \dots - x - 1 = 0$

$x^{47} + x^{46} + \dots + x + 1 = 2(x^{23} + x^{22} + \dots + x + 1)$

$\frac{x^{48} - 1}{x - 1} = 2\frac{x^{24} - 1}{x - 1}$

$x^{48} - 1 - 2x^{24} + 2 = 0$

$(x^{24} - 1)^2 = 0$

And we can proceed as above.

## Solution 3

As in Solution 1, we find that the roots of $P(x)$ we care about are the 24th roots of unity except $1$. Therefore, the squares of these roots are the 12th roots of unity. In particular, every 12th root of unity is counted twice, except for $1$, which is only counted once.

The possible imaginary parts of the 12th roots of unity are $0$, $\pm\frac{1}{2}$, $\pm\frac{\sqrt{3}}{2}$, and $\pm 1$. We can disregard $0$ because it doesn't affect the sum.

$8$ squares of roots have an imaginary part of $\pm\frac{1}{2}$, $8$ squares of roots have an imaginary part of $\pm\frac{\sqrt{3}}{2}$, and $4$ squares of roots have an imaginary part of $\pm 1$. Therefore, the sum equals $8\left(\frac{1}{2}\right) + 8\left(\frac{\sqrt{3}}{2}\right) + 4(1) = 8 + 4\sqrt{3}$.

The answer is $8+4+3=\boxed{015}$.

~rayfish

## Video Solution by Sal Khan

- AMBRIGGS

 2003 AIME II (Problems • Answer Key • Resources) Preceded byProblem 14 Followed byLast Question 1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 All AIME Problems and Solutions